Ground floors - Marshall, Duncan; Brown, Stephen; University of the West of England, Bristol. Faculty of the Built Environment (Bristol : Faculty of the Built Environment, University of the West of England, 2006)
This film, extensively revised in 2006, describes the variousforms of ground floor structure which are likely to be found in both existing and new housing. It explains the evolution of modern practice and materials and shows modern floors in the process of construction. The film introduces those criteria which affect floor selection and highlights some of the factors which can lead to premature floor failure
Title from title screen
Keywords: Floors; Underground construction